Noble lord, good shepherd : Episcopal power and piety in Aquitaine, 877-1050 - Jones, Anna Trumbore (Brill's series on the early Middle Ages ;, 2009)
This book examines the range of bishopsa (TM) activities in tenth- and eleventh-century southwest France, as they ruled their cathedrals, interacted with lay powers, patronized religious communities, and wrestled with the complex nature of their office.